1979
DOI: 10.1172/jci109401
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Secretion and Metabolism during the Perinatal Period in the Rat

Abstract: A B S T R A C T To better understand why plasma immunoreactive insulin (IRI) concentration is high in the rat fetus during the last 3 d of gestation and why fetal hyperinsulinemia abruptly subsides after birth, insulin secretion and metabolic clearance rates were estimated in fetuses and nursed pups.Intravenously injected ['251]monoiodoinsulin was cleared from the plasma of prematurely delivered pups at least as rapidly as from that of 7-to 10-d-old pups, suggesting that fetal hyperinsulinemia is not a result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1

Year Published

1980
1980
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 27 publications
4
17
1
Order By: Relevance
“…In the control rats, the plasma insulin level at the end of fetal life was found to be very high as compared to those in newborn and adult rats in accordance with previous studies [14][15][16]. Concerning the plasma glucagon level, it reached its highest value during neonatal life when compared to the fetal and adult age, in confirmation of previous reports [14,17].…”
Section: Discussionsupporting
confidence: 90%
“…In the control rats, the plasma insulin level at the end of fetal life was found to be very high as compared to those in newborn and adult rats in accordance with previous studies [14][15][16]. Concerning the plasma glucagon level, it reached its highest value during neonatal life when compared to the fetal and adult age, in confirmation of previous reports [14,17].…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, the fetal liver slowly expelled 1251-~yr, as evidenced by the sluggish decrease of total liver radioactivity over the period studied. In addition, in more mature fetuses, we have previously reported that the plasma concentration of IZ5I-Tyr Ins degradation products increased very slowly with time (17).…”
Section: Discussionmentioning
confidence: 83%
“…Based on this approach, several fetal organs, notably the liver and kidneys, appeared to concentrate insulin throughout the studied period of gestation. Insulin binding in the liver was inhibited by coinjection of 100 m u unlabeled insulin (saturable binding), whereas insulin uptake by the kidneys was not (unsaturable uptake) (16,17,18). The lungs appeared to concentrate significantly the labeled hormone in only the youngest fetuses.…”
Section: Resultsmentioning
confidence: 99%
“…As each fetus was exposed, a deep incision was made in the axillary region and blood was collected on ice while the placenta and umbilicus were still intact. The latter point is of importance since blood glucose and insulin values can alter rapidly in the rat fetus especially following severance of the umbilical cord (13). Blood from all animals within a single uterine horn, either ligated or control, was pooled before the centrifugation and separation of plasma which was stored at -20" C. After noting the position of each fetus within the uterus, they were weighed to an accuracy of 1 mg and the nose-tail length was measured by ruler to the nearest millimeter.…”
Section: Methodsmentioning
confidence: 99%